Cloud computing : a practical approach. - Velte, Anthony T., ....-; Elsenpeter, Robert, ....-; Velte, Toby J., ....- (New York : McGraw-Hill, 2010)
Chapter 1: The History and Future of Cloud Computing Chapter 2: Cloud Computing Basics Chapter 3: Your Organization and Cloud Computing Chapter 4:Cloud Computing with the Titans (Google, Microsoft, Amazon, Yahoo) Chapter 5: The Business Case for going Cloud (w/ case study) Section Two: Cloud Computing Technology Chapter 6: Hardware and Infrastructure Chapter 7: Accessing the Cloud (basics to APIs) Chapter 8: Cloud Storage Chapter 9: Emerging Standards Section Three: Cloud Computing at Work Chapter 10: Software as a Service Chapter 11: Software Plus Services Chapter 12: Developing Applications Chapter 13: Local Clouds and Thin Clients Chapter 14: Migrating to the Cloud Appendix A: Best Practices Appendix B: List of Cloud Computing movers and shakers and Informational Resources